Federalization, Ethnicity and Natural Resources: Debates on Nepal’s Rural Development (Research Nepal Journal of Development Studies, 2025)
The federal transformation of Nepal with its three-tier federal governance system, endowed to decentralize authority, recognize ethnic diversity, and enhance localized management of natural resources. This paper critically examines the intersections between federalization, ethnicity, and natural resource governance in rural Nepal by deploying systematic review and content analysis approach thereby accessing constitutional texts, legislative instruments, policy reports, and scholarly literature. It interrogates the legal and institutional frameworks shaping Indigenous peoples’ rights to land, territories, and resources, while highlighting the socio-political dynamics of marginalization rooted in caste, ethnicity, and geography. The findings reveal persistent pressure between state and ethnic communities in course of ownership, utilization and control over natural resources compounded by historical injustice, legal incompetencies, entrenched class and caste-based hierarchies and inconsistent policy implementation which is further intensified with intensified by climate change, demographic pressure and structural inequalities. This ultimately hinders equitable distribution of natural resources and social justice approach envisioned by federal model. The paper also figured out that despite of international commitments such as International Labor Organization (ILO) Convention No. 169 and the United Nation’s Declaration on the Rights of Indigenous Peoples (UNDRIP), implementation of commitment at the domestic level remains partial and inconsistent. The paper concludes that coherent multi-tier governance, stronger institutional capacity, and the integration of Indigenous knowledge into policymaking are essential to achieving inclusive, equitable, and sustainable natural resource management in rural development of federal Nepal